Exploration on the bio-recycling agent and its recycled asphalt: Composition ratio, recycling efficiency and micro-mechanism - Ying Fang; Zhengqi Zhang; Fei Zhou; Hengbin Liu; Zhongnan Tian (PLoS ONE, 2025)
Mineral oil-based asphalt recycling agents pose environmental concerns, prompting the search for sustainable alternatives. To this end, a bio-recycling agent (BRA) based on waste vegetable oil (WVO) was initially designed for the utilization of recycled asphalt pavement (RAP) through the orthogonal test, and then its physical-chemical and permeating properties were analyzed by a series of tests. Next, the bio-recycled asphalt binder was prepared and its several pavement behaviors were measured via adhesion, rheology and fatigue experiments, thus its recycling efficiency was validated. Ultimately, the microscopic mechanism of bio-recycled asphalt was revealed with differential scanning calorimetry (DSC) and atomic force microscope (AFM) tests. Research results showed that the composition of BRA was determined as base oil components: permeation components: polymer components: functional components = 120: 2: 13: 2.4. Compared to two commercial recycling agents (LBS and HRA), BRA possessed better recycling effect at the same dosage, which obviously restored the adhesion, high- and low-temperature rheological properties and fatigue resistance of aged asphalt, and the BRA increased fatigue life of aged matrix asphalt binder by about 60% compared to LBS at 9% dosage. Moreover, the recycled asphalt with suitable BRA dosage can adapt to a wider range of traffic grades than original asphalt, and for aged matrix and SBS-modified asphalt binder, it was recommended that the reasonable dosage of BRA was 7%−9% and 3%−5%, respectively. The samples recycled by three recycling agents all exhibited favorable thermal stability, and which was basically the same as or higher than that of the original asphalt. Besides, after incorporating the BRA, the number and size of bee-structures in aged asphalt decreased, while the roughness of asphalt surface slightly descended. Meanwhile, compared to two-commercial recycling agents, BRA had a significant improvement on the micro adhesion of aged asphalt, and behaved a better recycling effect on the aged asphalt.